PENGARUH SISTIM PENGHARGAAN DAN EMOTIONAL QUOTIONS TERHADAP KINERJA MELELUI PRESTASI KERJA TENAGA PENGAJAR DI SMK AHMAD YANI KOTA PROBOLINGGO - jurnalmap map; Ngatina ÔÇÄ; Mei Indrawati; Chandra Kartika (MAP (Jurnal Manajemen dan Administrasi Publik), 2020)
This study examines the decline in the performance of teaching staff in carrying out their duties as teachers. The purpose of this study is to know the extent of appreciation and emotional quotions in improving performance through the work performance of teaching staff at SMK AHMAD-YANI Probolinggo City. Analysis of the data used in this study is to test the path analisyis to determine the direct influence and indirect influence between the independent variable and the dependent variable. The results of this study show that there are significant and positive influences between rewards and performance as well as the work performance of teaching staff and awards can improve performance through work performance. Emotional quotions have a positive and significant effect on performance and work performance with emotional control questions are good able to improve performance through the work performance of teaching staff. Award and Emotional quotions can improve teaching staff performance together through work performance. Keywords: awards, emotional quotions, job performance